Novel "in-house" Chemical Treatments of Pomegranate Peel (Punica granatum) for Simultaneous Heavy Metal Removal - Krečo, Anes (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
The growing movement in environmental chemistry is looking for a way to remove heavy metals from wastewater by using agricultural waste as biosorbents. The fact that pomegranate (Punica granatum) fruit leaves behind significant amounts of waste biomass after consumption makes it an exceptional candidate for reuse as sorbent material. This study presents the development of 2 novel "in-house" chemical modification processes of powdered dry biomass, focusing on the synthesis and classification of the products of different procedures, with the aim of maximizing the simultaneous removal efficiency of Cr3+, Cu2+, Mn2+, Co2+, Ni2+, Cd2+, Pb2+ and Zn2+ from water solution. Modification as well as biosorption of metals has been successfully confirmed by FTIR and SEM-EDS techniques based on determination of functional groups, morphological characterization by mapping of metal distribution on the pomegranate surface, along with its semi-quantitative elemental analysis. It has been shown that under optimal biosorption parameters the removal efficiency for the selected biosorbent of the eight selected heavy metal ions was in the following range: Cu2+ ≈ Pb2+ > Cr3+ > Cd2+ > Zn2+ > Ni2+ ≈ Co2+ > Mn2+.